PERANCANGAN STRATEGI CORPORATE SOCIAL RESPONSIBILITY BIDANG PENDIDIKAN PT ASURANSI MSIG INDONESIA MELALUI BALANCED SCORECARD - Putri - Vionita; Lindawati - Kartika (Admisi dan Bisnis, 2016)
PT MSIG has the goal of becoming a No. 1general insurance company in the region interms of acquisition of premium income andquality of service. The purpose of this studyare: (1) Designing organizational alignmentprocess in the field of educational CSRprogram at PT MSIG. (2) Designing strategymaps based on BSC approach. (3) Measuringperformance achievement and initiativesstrategic on educational CSR program at PTMSIG in 2015. This study used nonprobabilitysampling method with purposive techniqueand probability sampling method with censustechnique. Research methods and dataanalysis based from balanced scorecard withthe assistance Microsoftexcel 2007. Theresults of this studies indicated thatperformance of the CSR program at PT MSIGhas been good with 89.81% value expressedin green. This performance can be maintainedand improved by implementing a program ofinitiatives strategic, especially on the KeyPerformance Indicators that have not yetreached the very good category.